2013
DOI: 10.1093/ejcts/ezt024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiofrequency ablation and comparison with surgical sympathectomy in palmar hyperhidrosis

Abstract: This is the first clinical study to evaluate the role of radiofrequency ablation and compare it with the surgical treatment option for palmar hyperhidrosis. Radiofrequency ablation significantly decreased hyperhidrosis, but it had a lower success rate than surgical sympathectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 18 publications
0
27
3
Order By: Relevance
“…Portuloglu et al had a 75% success rate in a percutaneous technique and 95% rate in a video-assisted thoracoscopy technique 62. Fouad obtained a rate of 90% improvement in sweating in his series of ten cases submitted to T2 ganglion lesion 64…”
Section: Palmar Hyperhidrosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Portuloglu et al had a 75% success rate in a percutaneous technique and 95% rate in a video-assisted thoracoscopy technique 62. Fouad obtained a rate of 90% improvement in sweating in his series of ten cases submitted to T2 ganglion lesion 64…”
Section: Palmar Hyperhidrosis Treatmentmentioning
confidence: 99%
“…It is usually performed in outpatient clinics or day-hospital regimens, with low morbidity and satisfactory results in the control of pain syndromes (Figure 6). 55 , 56 , 61 , 62…”
Section: Palmar Hyperhidrosis Treatmentmentioning
confidence: 99%
“…Purtuloglu et al studies also showed similar results. [11,12] Clipping is a sympathetic blockage technique which has been performed widely for the treatment of hyperhidrosis. It is similar to other sympathetic activity denervation techniques such as coagulation, cutting and segment removing in regard of safety, efficiency and feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…Under fluoroscopic guidance, 10-cm lenght and 5-mm diameter active Treatment of compensatory hyperhidrosis of the trunk with radiofrequency ablation Table 1. Classification of compensatory hyperhidrosis [12] Classification Feature…”
Section: Rf Techniquementioning
confidence: 99%
“…In addition to pharmacologic therapy, other treatments include surgical sympathectomy, radiofrequency ablation, 41 surgical excision of the affected areas, and subcutaneous liposuction.…”
Section: Botulinum Toxinmentioning
confidence: 99%